The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1044/2014_ajslp-13-0074
|View full text |Cite
|
Sign up to set email alerts
|

Segmental and Prosodic Approaches to Accent Management

Abstract: Accent management, consisting of both segmental and prosody training, yielded positive outcomes. Further research with native language speakers of other languages is important to verify and expand on these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Our study shows that, apart from boosting students’ phonological awareness and reading skills in their native language (Bhide et al, 2013), short rhythmic hand-clapping activities can be especially beneficial in the context of second language pronunciation instruction. In this context, the findings of this study provide additional support for the importance of an explicit, global, suprasegmental approach to L2 pronunciation instruction (Behrman, 2014; Derwing & Rossiter, 2003; Derwing et al, 1998; Gordon et al, 2013).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our study shows that, apart from boosting students’ phonological awareness and reading skills in their native language (Bhide et al, 2013), short rhythmic hand-clapping activities can be especially beneficial in the context of second language pronunciation instruction. In this context, the findings of this study provide additional support for the importance of an explicit, global, suprasegmental approach to L2 pronunciation instruction (Behrman, 2014; Derwing & Rossiter, 2003; Derwing et al, 1998; Gordon et al, 2013).…”
Section: Discussionsupporting
confidence: 55%
“…However, recent work has pointed to the need for L2 prosodic instruction, given that having incorrect prosody in the L2 may result in higher ratings of accentedness comprehensibility and intelligibility issues (for a review, see Anderson-Hsieh, Johnson & Koehler, 1992; Derwing & Munro, 2009). Several studies have highlighted the importance of suprasegmental instruction for improving learners’ overall fluency and comprehensibility and reducing their foreign accent (see, for example, Behrman, 2014; Derwing & Rossiter, 2003; Derwing, Munro & Wiebe, 1998; Gordon, Darcy & Ewert, 2013). Yet while suprasegmental training has proven to be successful in improving second language learners’ overall fluency and comprehensibility, almost no work has tested the efficacy of suprasegmental training paradigms on specific pronunciation issues.…”
Section: Introductionmentioning
confidence: 99%
“…Behrman (2014) also compared the effects of segmental and prosody training on reducing speakers’ foreign accent. Segmental training focused on the articulation of consonants, while prosodic training focused on four prosodic utterance levels: rise-fall pitch in one-word utterances, rising, falling, and rise-fall intonation in three-word utterances, informational and yes/no questions, and prosodic rhythm of longer utterances.…”
Section: Introductionmentioning
confidence: 99%
“…Fritz and Sikorski (2013), for example, presented evidence that Korean participants in a university accent modification program made significant gains both in terms of overall intelligibility and confidence in their ability to communicate effectively. Similarly, in a single-subject, alternating-treatment design, Behrman (2014) found that accent modification training resulted in gains in intelligibility and ease of understanding for four Hindi-speaking participants. They also found that directly targeting segmentals (in this case, consonants) had a direct effect on the accuracy of their participants' consonant production, and directly targeting prosody had a direct effect on the accuracy of their participants' production of American English prosody, suggesting the potential importance of targeting each of these broad areas.…”
mentioning
confidence: 87%
“…Although research has been conducted on the efforts of nonnative speakers to change or improve their English pronunciation, most of it has come from researchers who are investigating the effectiveness of instruction strategies in English-as-a-second-language (ESL) classrooms (e.g., Derwing, Munro, & Wiebe, 1998;Derwing & Rossiter, 2003). As Behrman (2014) pointed out, there are potential difficulties generalizing these findings to accent modification training provided by SLPs, where clients are typically more proficient in the English language than in an ESL setting, and training is more individualized than is possible in the context of an ESL classroom.…”
mentioning
confidence: 99%